Pengaruh Keragaman Produk dan Layanan Toko Terhadap Tingkat Kepuasan Pelanggan pada Toko Alizah Mart Sengkang - Siardin Andi Djemma; Andi Bakti; Ahmad Muktamar; Hakidah Hakidah (Institute of Advanced Knowledge and Science, 2023)
The focus of the research is to find out whether the variety of store products and services can influence customer satisfaction both directly and indirectly so that it can provide added value and provide information needs in improving the quality of everything offered by the Alizah Mart Sengkang Store. The population of this research is all customers who carry out purchasing activities at the Alizah Mart Sengkang Store. The total sample was 64 people. The sampling technique uses the Slovin formula. Data collection techniques use questionnaires and direct interviews. Data collection methods used descriptive analysis and multiple linear regression. The research results show that the constant coefficient value is 1.849, while the value of the product diversity regression coefficient is 0.323 and the store service regression coefficient is 0.587, so the multiple linear regression equation is Y = 1.849 + 0.323X1 + 0.587X2. The results of the partial hypothesis test show that t calculated from product diversity is 2.263 > t table 1.999, which means product diversity influences customer satisfaction, and t calculated from store service is 5.120 > t table 1.999, which means store service influences customer satisfaction. The results of the coefficient of determination were 50.1% and the product diversity correlation coefficient was 0.535, which means a moderate level of close relationship, while the store service correlation coefficient was 0.677, which means a strong level of close relationship.